ORGANISASI PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA SEBAGAI SARANA PEMBERDAYAAN PEREMPUAN - Aslichati, Lilik (Jurnal Organisasi Dan Manajemen, 2011)
This study aims to assess the effectiveness of PKK as a means of empowering women to achieve the Millennium Development Goals (MDG's). Research sites are the PKK of Pasar Minggu district, South Jakarta and the PKK of Ciputat district, South Tangerang city. The results showed that PKK is an organization that is potentially a means of empowerment and equal participation of women in development effectively. All of work programs are oriented to the empowerment of women, although implementation is still in top down orientation, not bottom up as expected. The PKK is also only able to empower female members only, not to have an impact on the empowerment of women non-members. Nevertheless the benefits are felt by the surroundings community, especially the Posyandu programs for the toddlers and the elderlies. The targeted, measurable, and intensive trainings as well as support from the local governments are still required in order to empower women through the PKK.